Machine Learning Sustainable Competitiveness for Global Recovery - López-Fernández, Andrée Marie; Terán-Bustamante, Antonia; Martínez Velasco, Antonieta Teodora (My University, 2022)
The unexpected appearance and expansion of the pandemic caused by COVID-19 have shown that both developed and less developed countries need strategic, scientific-technological capacities and an innovation ecosystem to respond quickly to these challenges. The objective of this research is to analyze the potential correlation between competitiveness and sustainable development for a global recovery. To carry out the study, five global indexes were considered: competitiveness, sustainability, innovation, impunity, and human development which were analyzed with a mixed-method approach, quantitative and qualitative analysis. Organizational and government leaders are facing significant collateral effects of the health pandemic including economic recession and social development regression; therefore, the road to recovery requires they work toward sustainable development to reach desired competitiveness. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: International business enterprises; International economic integration; Globalization